2021
DOI: 10.1021/acsearthspacechem.0c00339
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Hygroscopic Characterization of Surface Salts in the Qaidam Basin: Implications for Climate Impacts on Planet Earth and Mars

Abstract: Salt particles play important roles in many atmospheric processes due to their high hygroscopicity. Saline lakes and playas are sources of salt particles, which are normally mixed with mineral dust that can be transported over long distances. In this study, salt samples collected from four saline lakes and surrounding playas in the Qaidam Basin are studied for their physicochemical properties, focusing on the chemical compositions and hygroscopicity. The salt samples include brines, lakebed salts, crust salts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 76 publications
(157 reference statements)
6
23
0
Order By: Relevance
“…In the latter case, reversible surface solvation was only observed when the RH approaches the deliquescence RH. Furthermore, no resolvable mass changes were observed for these RHs in a previously reported hygroscopicity study of the Qaidam salts, 9 which again supports the argument that the observed phenomena are surface specic.…”
Section: Surface Solvation At Low Rhsupporting
confidence: 86%
See 4 more Smart Citations
“…In the latter case, reversible surface solvation was only observed when the RH approaches the deliquescence RH. Furthermore, no resolvable mass changes were observed for these RHs in a previously reported hygroscopicity study of the Qaidam salts, 9 which again supports the argument that the observed phenomena are surface specic.…”
Section: Surface Solvation At Low Rhsupporting
confidence: 86%
“…In addition, no further changes are observed in the magnesium spectrum from RH = 5% to 20%, implying that even trace levels of water vapor (RH = 5%) are already enough to completely alter the physicochemical environment on the surface of the salt mixtures. Note that for these RHs, no detectable mass changes were reported from hygroscopicity measurements in a previous study, 9 indicating that this surface solvation is only occurring in the topmost surface layers.…”
Section: Brines and Lakebed Saltsmentioning
confidence: 58%
See 3 more Smart Citations